Pediatric Basilar Skull Fracture Mechanisms and Trends From 2007 to 2018. (June 2021) - Magit, Anthony; Stramiello, Joshua A.; Good, Raquel; Nation, Javan
Objectives: To evaluate the specific mechanism and trend of injury resulting in pediatric basilar skull fractures. Study Design: Retrospective chart review of a trauma database. Setting: Tertiary care children's hospital. Methods: Patients ≤18 years old with basilar skull fractures were identified via the trauma database for admissions from 2007 to 2018. Patients were identified with ICD-9 codes (801.0, 801.1, 801.2, 801.3 or 801.4) and ICD-10 codes (S02.1, S02.10, S02.11, S02.19) for skull base fractures ( International Classification of Diseases, Ninth Revision and Tenth Revision ). Results: A total of 729 patients were included: 251 females and 478 males. The 2 most common mechanisms of injury are multilevel falls and unhelmeted rider falls. Multilevel falls occur more in the toddler age group (average age, 4 years), and unhelmeted rider falls are seen in the older age group (average age, 11.2 years). Helmeted rider and motor vehicle accident basilar skull injuries are relatively uncommon. There was a spike in television/entertainment center mechanisms of injury in toddlers from 2007 to 2011 but has since decreased. Conclusion: Pediatric basilar skull fractures are costly to the health care system, as patients spent more time in intensive care unit beds with a charge limited to hospital rooms between $1.7 and $2.7 million per year. The protective effect of helmets is demonstrated by unhelmeted rider injuries being the second-most common mechanism of basilar skull fractures and by helmeted rider injuries being rare. The small proportion of basilar skull fractures from motor vehicle accidents is an example of policy and behavioral changes resulting in decreased injury.